(untitled) (Research, Society and Development, 2021)
Objective: bibliographically, it aims to verify the insertion of the pharmacist in primary health care, demonstrating their role. Methods: bibliographical in nature, mediated from primary studies recruited from scientific articles and journals, it advocates the descriptive integrative review method, with a quali-quantitative approach. Results: through the analysis of data recruited here, it was noticeable to determine that the insertion of the pharmacist in primary health care is of fundamental importance for the public health of the Brazilian federation. Conclusion: The evidence that actions, aimed at the insertion of the professional pharmacist, is of paramount relevance, which corroborates for a better quality of life of individuals requesting care in primary health care. Another important factor is that pharmaceutical insertion has greatly influenced primary health care, making it necessary for public health management to value the services provided by these collaborators of human health, so that the misuse of medicines is minimized preventing possible harm to public health.